Dampak Penambangan Timah di Laut Terhadap Ekosistem Terumbu Karang di Pulau Pemuja dan Malang Duyung, Kabupaten Bangka Barat, Provinsi Kepulauan Bangka Belitung - Indra Ambalika Syari; Mohammad Agung Nugraha; Mu’alimah Hudatwi (Universitas Bangka Belitung, 2022)
The Province of the Bangka Belitung Islands has an ocean area of 79.9% which has the potential for fisheries and tourism as well as tin mining in the sea. This research was conducted in October 2020 in the coral reef ecosystem of Pemuja Island (near to the coastal) and Malang Duyung Coral (far to the coastal), West Bangka Regency. The method used is Line Intercept Transect (LIT). The results showed that the condition of the coral reefs on Pulau Pemuja was categorized as